KKN-PPM Pengembangan Usaha Ternak Unggas Non Ayam pada Kelompok Tani di Desa Baumata Timur - Malelak, Gemini Ermiani Mercurina; Lestari, Gusti Ayu Yudiwati; Ratu, Maria Rosdiana Deno; Jelantik, I Gusti Ngurah (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
The purpose of the KKN-PPM program is to increase the knowledge of the breeders about a proper duck raising system. The method of implementation in the field includes counseling, training and assistance, and program monitoring and evaluation. The evaluation phase is carried out on the performance of students by measuring the effective working hours of students (JKEM) which include the main activities, individual and social, and measuring the level of technology adoption by farmers using questionnaires and interviews. Interviews were conducted with 45 members of farmer groups, interviewed with questionnaire guidelines. The results of the KKN-PPM activities are that each participant has spent an effective amount of student work totaling 169 hours consisting of main activities 86 hours (± 50 percent), for individual activities of 52 hours (± 30 percent) and social activities of 31 hours (± 20 percent). The highest adoption rate of breeders was in the types of livestock raising activities 95.56 percent and livestock health 88.89% while for fermentation, hatching and egg processing activities the adoption rates were 62.22 percent, 66.67 percent and 77.77 percent. The level of adoption of farmers for the technology provided is influenced by factors in the agricultural system they live in, there are other social activities that affect the availability of time to carry out their farming activities and whether there are additional costs if they use the technology. How to cite:Malelak, G. E. M., Lestari, G. A. Y., Ratu, M. R. D., Jelantik, I. G. N. (2020). KKN-PPM Pengembangan Usaha Ternak Unggas Non Ayam pada Kelompok Tani di Desa Baumata Timur. Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 5(1), 85-92.DOI: https://doi.org/10.26905/abdimas.v5i1.3589